Body dimensions of elite handball players with respect to laterality, playing positions and playing standard - Karcher, C.; Ahmaidi, S.; Buchheit, M. (Journal of Athletic Enhancement, 2014)
Purpose: The aim of the present study was to examine, using a large player database, between-playing positions and playing standard differences in body dimensions.